2020
DOI: 10.1096/fj.202001386r
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid activated receptors GPBAR1 and FXR exert antagonistic effects on autophagy

Abstract: Autophagy is a highly conserved catabolic process activated by fasting and caloric restriction. FXR, a receptor for primary bile acids, reverses the activity of cAMP‐response element binding protein (CREB) on autophagy‐related genes (Atg)s and terminates autophagy in the fed state. GPBAR1, a receptor for secondary bile acids, exerts its genomic effects via cAMP‐CREB pathway. By genetic and pharmacological approaches, we have obtained evidence that GPBAR1 functions as a positive modulator of autophagy in liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Bile acids are signaling molecules that can activate nuclear hormone receptors including FXR and TGR5 (also known as GPBAR1), which is a cell-surface receptor of the G protein-coupled receptor family[ 73 ]. These two bile acid receptors have been described to modulate autophagy in the liver and adipose tissue in fed and fasted states[ 74 ].…”
Section: Systemic Effects Of the Gut Microbiota On Host Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acids are signaling molecules that can activate nuclear hormone receptors including FXR and TGR5 (also known as GPBAR1), which is a cell-surface receptor of the G protein-coupled receptor family[ 73 ]. These two bile acid receptors have been described to modulate autophagy in the liver and adipose tissue in fed and fasted states[ 74 ].…”
Section: Systemic Effects Of the Gut Microbiota On Host Autophagymentioning
confidence: 99%
“…Several alterations of autophagy, including a decreased amount of LC3 mRNA and LC3-II and an increased amount of p62, have been observed in the liver of mice fed a high-fat diet (HFD), a potent inducer of dysbiosis[ 74 ]. Chronic exposure of rats to an HFD can lead to NASH (non-alcoholic fatty steatohepatitis).…”
Section: Systemic Effects Of the Gut Microbiota On Host Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, atherosclerotic lesions can be promoted by feeding a high fat diet in combination with CA that is the main FXR agonist in mice, highlighting the central role of FXR‐mediated inhibition of CYP7A1 in preventing cholesterol disposal in mice 32 . Consistent with the detrimental role of FXR in regulating cholesterol disposal in mice, MCAs that remove inhibition of FXR on CYP7A1 have been identified as one of the effectors that confers resistance against hypercholesterolemia in rodents feed a cholesterol‐reach diet 16,33,34 …”
Section: Introductionmentioning
confidence: 99%
“…32 Consistent with the detrimental role of FXR in regulating cholesterol disposal in mice, MCAs that remove inhibition of FXR on CYP7A1 have been identified as one of the effectors that confers resistance against hypercholesterolemia in rodents feed a cholesterol-reach diet. 16,33,34 Building on this background, we have investigated whether modulation of cholesterol biosynthesis by atorvastatin impacts on bile acid homeostasis in a mice model of NAFLD and we have compared the effect of atorvastatin to obeticholic acid, a potent FXR ligand advanced into phase 3 clinical trials in NAFLD/NASH. Our results have also shown that atorvastatin resets bile acid signaling and promotes formation of bile acid species that are GPBAR1 agonists.…”
Section: Introductionmentioning
confidence: 99%